The Influence of Tourist Attractions, Available Facilities, and Accessibility on the Decision of Domestic Travelers to Visit The Kaldera Toba - Aji Prabowo; Arisman Parhusip; Montaris Silaen (Journal of Management and Business Analytics, 2025)
Lake Toba, with its calm waters, green hills, and refreshing air, is a perfect destination for relaxation. One of its standout attractions is The Kaldera Toba Nomadic Escape, developed by the Ministry of Tourism in Sibisa Village, Ajibata District, Toba Regency. This study investigates the impact of attractiveness, facilities, and accessibility on domestic tourists' decisions to visit The Kaldera Toba Nomadic Escape, both individually and collectively. Applying a quantitative approach, data were gathered through surveys and observations from 100 domestic tourists who visited between 2022 and 2023. The results indicate that all three factors significantly affect tourists' visiting decisions. Attractiveness recorded a t-value of 17.309 (significance 0.000), facilities had a t-value of 3.152 (significance 0.002), and accessibility showed a t-value of 2.830 (significance 0.000). Additionally, these factors collectively exert a strong influence, as reflected in an F-value of 182.395 (exceeding the F-table value of 3.09) with a significance level of 0.000. The model explains 84.6% of the decision-making process, while the remaining 15.4% is attributed to other factors.